Synonyms in the Arabic language: (Studying models from the Noble Qur’an and according to Abu Hayyan Al- Andalusi through his interpretation of the Qur’anic verses) - Adam, Fathelrahman Elneem (Journal of Humanities & Social Sciences, 2021)
This study dealt with one of the important language issues, which is the synonymy in the Arabic language and the Qur’an, studying models from the Holy Qur’an and according to Abu Hayyan Al- Andalusi through his interpretation of the Qur’anic verses in directing the linguistic and lexical connotations of the Qur’anic vocabulary; In order to reach the connotations that fall under it, which had the effect of enriching the meaning in the language; This is by examining: the concept of synonymy, linguistically and idiomatically, and the scholars’ position on it in terms of acknowledging its existence and non- existence, as well as synonymy in the Holy Qur’an and its call to clarify the differences between words, and Abu Hayyan al- Andalusi’s position on synonymy and his acknowledgment of its existence. And the result of this is clear in his interpretation of (exploded, Spout and split), saying: And the apparent use of the Qur’an is to use them in one sense because the two verses are one story, as it looked at the apparent meaning of the lexical more than it looked at the word in its context, and one of the results of the dispute that erupted between scholars, ancient and modern on the issue The meaning of synonymy and its proof and denial is mainly due to its extreme importance and the need to take care of it. The synonymous word is the one whose connotation converges with others in the general meaning. Among the peculiarities of the connotation is what we do not discover except in its context in which it is mentioned. All of its meanings, rather the expression is expressed with a word that approximates its meaning. Otherwise, the Qur’anic challenge would not be for the fluent language people, and therefore the synonymy is very few in the language and the Qur’an.